Association between water and sanitation service levels and soil-transmitted helminth infection risk factors: a cross-sectional study in rural Rwanda - Mather, William; Hutchings, Paul; Budge, Sophie; Jeffrey, Paul (Oxford University Press, 2020)
Soil-transmitted helminth (STH) infections are one of the most prevalent neglected tropical diseases in the world. Drug treatment is the preferred method for infection control yet re-infection occurs rapidly, so water and sanitation represent important complementary barriers to transmission. This cross-sectional study set out to observe STH risk factors in rural Rwandan households in relation to the Sustainable Development Goal water and sanitation service levels. Survey and observation data was collected from 270 households and 67 water sources in rural Rwanda and was processed in relation to broader risk factors identified from the literature for the role of water and sanitation in STH infection pathways. The study found a significant association between higher water and sanitation service levels and lower STH infection risk profiles for both water and sanitation. However, variability existed within service level classifications, indicating that greater granularity within service level assessments is required to more precisely assess the efficacy of water and sanitation interventions in reducing STH infection risks.
Keywords: Rwanda; soil-transmitted helminth; sanitation; neglected tropical diseases; water